2015
DOI: 10.1007/s00066-015-0854-y
|View full text |Cite|
|
Sign up to set email alerts
|

Re-irradiation with cetuximab or cisplatin-based chemotherapy for recurrent squamous cell carcinoma of the head and neck

Abstract: Both cetuximab- and cisplatin-based ReRT of SCCHN recurrences are feasible and effective treatment options with comparable results in terms of tumour control and survival. Acute adverse events may differ slightly. Our prognostic score could help to identify appropriate patients for ReRT and stratify patients within future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
(49 reference statements)
3
17
0
2
Order By: Relevance
“…Again, the outcomes were quite promising taking into account that the recurrent tumors were more advanced than in our previous study. loco-regional control rate inside the re-irradiated areas of 75% was at the top of the range of 44-80% found in other studies (15)(16)(17)(18)(19)(20). And the 1-year survival rate of 50% was well in the range of 33% to 77% reported in the other studies.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Again, the outcomes were quite promising taking into account that the recurrent tumors were more advanced than in our previous study. loco-regional control rate inside the re-irradiated areas of 75% was at the top of the range of 44-80% found in other studies (15)(16)(17)(18)(19)(20). And the 1-year survival rate of 50% was well in the range of 33% to 77% reported in the other studies.…”
Section: Discussionmentioning
confidence: 53%
“…The chemoradiation regimen used in the present study was well tolerated; grade 3 toxicities were not observed. In other studies, grade 3 or greater toxicities were reported in up to 36% of patients and treatment-related deaths in up to 12% of patients (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These results must also be considered in the context of trials in which radiation therapy has been re-administered to previously irradiated patients who present with LRHNC. Dornoff et al report 1 year overall survival rates for RT with cetuximab of 44.4% and of RT with cisplatin of 45.5% in a cohort of 66 re-irradiated patients with LRHNC (Dornoff et al, 2015). Other studies have yielded similar results with reports of median progression-free survival from re-irradiation of 15.0 months (Mallick et al, 2014) to 2 year overall survival rates of 43% (Riaz et al, 2014).…”
Section: Discussionmentioning
confidence: 75%
“…Abbreviations: Cet., cetuximab; NR, not reported; RT, radiotherapy; SBRT, stereotactic body radiotherapy …”
Section: Discussionmentioning
confidence: 99%